Mixing and Stiring in Aerated Stirred Tank Bioreactor - MOHD FAUZI , NOOR AKHMAZILLAH (2024)
Fermentation is a metabolic process carried out by microorganisms like yeast or bacteria and involves the conversion of sugars into other compounds such as acids, gases, or alcohol. This process is widely used in food production, and also utilized in industrial processes to produce various chemicals and pharmaceuticals. It is a fundamental aspect of biotechnology, food science, and microbiology, playing a crucial role in the production of many everyday products.Mixing is crucial in fermentation to ensure even distribution of nutrients, oxygen supply for aerobic processes, efficient contact between microorganisms and substrate, heat dissipation, and prevention of stratification, ultimately leading to optimal product quality and yield. This book provides a deeper understanding on the various mechanisms employed for agitation in stirred tank fermenters, such as impellers, baffles, and spargers. Also, analyzing the power consumption associated with stirring and mixing operations, including factors such as impeller design, rotational speed, and viscosity of the fermentation broth.The primary aim of this book is to be a comprehensive volume for stirring and mixing topic, ensuring that students not only grasp the fundamentals but also explore into the depths of understanding. With clear explanations and comprehensive notes, this book attempt to clarify the path toward mastery in this interesting topic.